PEMBUATAN KARBON AKTIF MONOLIT DARI KAYU KARET MENGGUNAKAN AKTIVATOR KOH DAN HNO3 UNTUK APLIKASI SUPERKAPASITOR - Zulkifli '; Erman Taer; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Activated carbon  monolith  (ACM)  was made  from  rubber  wood  for supercapacitor  applications  by using  two  activators,  namely  KOH  and  HNO3 . Carbonized sample were by N2 gas at a temperature of 600º C and were physically activated  by  CO2gas  at  800º C  for 2  hours.  KOH solution  of  1,  3  and  5M  was used  as  chemical  activation  solution.  ACM  electrodes  were tested  in  a two-electrode system,  which was stainless steel  as a  current  collector  and a 1M  H2SO4 solution  as  an  electrolyte  solution.  Electrochemical characterization  results by impedance  spectroscopy  methods  showed an increase  in the  capacitive  properties, followed by  a decrease in  cells  resistance. The  measurements  obtained the best capacitance  of  55.46  F/g.  XRD  patterns of  the samples showed  amorphous structure  and  SEM images  showed that  the  addition of  KOH  solution  resulted in the  pore  structure  of macroporous  and  mesoporous  combination.  In conclusion, this current result showed that the activator of KOH and HNO3have improved the performance of the ACM rubber wood electrode.